When Hysteroscopy is the only way out; a case series of endometrial osseous metaplasia - John Imaralu; Taiwo Solaja; Oluwole Ayegbusi; Olukemi Grillo; Remilekun Atunrase-Sotola; Theophilus Elejere (Babcock University Medical Journal)
Background: Endometrial osseous metaplasia (EOM) poses diagnostic and treatment dilemmas. Hysteroscopy is the gold standard in the diagnosis of endometrial pathologies and offers optimal treatment for osseous metaplasia.